2022
DOI: 10.36408/mhjcm.v9i1.696
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Penggunaan Shoulder Bag Dengan Kejadian Trapezius Myalgia

Abstract: LATAR BELAKANG : Trapezius Myalgia merupakan penyakit dengan prevalensi yang meningkat, khususnya pada kelompok usia produktif (15-64 tahun). Di Indonesia kasus trapezius myalgia kurang mendapat perhatian karena kurangnya publikasi dan sering tidak terdiagnosis. Trapezius Myalgia terjadi karena kurangnya oksigen pada otot trapezius sehingga memicu metabolisme anaerobik dan menyebabkan pelepasan mediator nyeri. Beberapa faktor risiko diyakini dapat menimbulkan trapezius myalgia, antara lain jenis kelamin, beban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Subsequently, muscles activated anaerobic metabolism to obtain energy, causing the release of pain mediators. 22 The duration of usage and backpack weight simultaneously or together influenced shoulder pain complaints. Alaa'Osaid's study (2012) in Turkey with a sample of 800 students concluded that wearing a backpack for 5-30 minutes/ day from home to school with an average backpack weight of 5.267 kg or 12.3% of their body weight caused shoulder pain (47.8%), lower back pain (21.6%), and neck pain (18.2%).…”
Section: Original Articlementioning
confidence: 99%
“…Subsequently, muscles activated anaerobic metabolism to obtain energy, causing the release of pain mediators. 22 The duration of usage and backpack weight simultaneously or together influenced shoulder pain complaints. Alaa'Osaid's study (2012) in Turkey with a sample of 800 students concluded that wearing a backpack for 5-30 minutes/ day from home to school with an average backpack weight of 5.267 kg or 12.3% of their body weight caused shoulder pain (47.8%), lower back pain (21.6%), and neck pain (18.2%).…”
Section: Original Articlementioning
confidence: 99%